Community Financial Institutions in Bali: Some empirical findings - Detlev Holloh (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1994)
The Lembaga Perkreditan Desa (LPD) in Bali are the most recent form of local finance in Indonesia. Their establishment was initiated by the provincial government of Bali after several studies on local financial institutions in Indonesia had been presented at a seminar carried out by the Ministry of Home Affairs in 1984. By 1992, the government had established 650 of the 1,600 LPDs planned to be set up in each desa adat (custom village).
Keywords: 330; Informeller Finanzsektor; Gemeinde; Bali